Optimization of the Role of Community Service Program (KKN) in Building Civic Awareness and Empowering the Community of Timbang Lawan Village - Lembayung Aurandyta; Noor Azizah; Khoiriyah Syaharani; Ghadief Hanbal (Academic Solution Publisher, 2025)
This study examines the optimization of the Community Service Program (Kuliah Kerja Nyata or KKN) as a transformative model for strengthening civic awareness and empowering the community of Timbang Lawan Village, Langkat Regency, Indonesia. Using a qualitative descriptive approach, data were collected through observation, interviews, focus group discussions, and documentation involving students, village officials, and community members. The findings reveal that the KKN program serves as an effective platform for promoting civic values, participatory learning, and sustainable development. Religious and social engagement activities such as the Muharram Festival and literacy mentoring enhanced civic consciousness and social solidarity. Economic empowerment through eco-printing, health education via Apotek Hidup, and environmental awareness through village tourism collectively built a culture of cooperation and self-reliance. The study concludes that the success of KKN depends on participatory collaboration, value integration, and institutional sustainability. Therefore, optimizing KKN as a civic empowerment framework strengthens not only academic-community partnerships but also contributes to Indonesia’s broader agenda of inclusive and sustainable nation-building.